2014
DOI: 10.1038/ng.3117
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analyses provide insights into the history of tomato breeding

Abstract: The histories of crop domestication and breeding are recorded in genomes. Although tomato is a model species for plant biology and breeding, the nature of human selection that altered its genome remains largely unknown. Here we report a comprehensive analysis of tomato evolution based on the genome sequences of 360 accessions. We provide evidence that domestication and improvement focused on two independent sets of quantitative trait loci (QTLs), resulting in modern tomato fruit ∼100 times larger than its ance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
800
5
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 796 publications
(902 citation statements)
references
References 49 publications
29
800
5
9
Order By: Relevance
“…Mapping of these genes on the reference genome of S. lycopersicum 'Heinz 1706' showed that considering the number of genes on each chromosome there was a relatively higher concentration of these defence genes on chromosomes 1, 5, 8, 9 and 10. Intriguingly, there was no overlap with previously analysed genomic locations of domestication sweeps, but on chromosomes 1 (2), 2 (3) and 8 (4) there was an overlap with the genomic locations of improvement sweeps analysed and described in another recent study (Lin et al, 2014) (Fig. 2A).…”
Section: Selection Of Genes Involved In Tomato Defence Responsessupporting
confidence: 53%
“…Mapping of these genes on the reference genome of S. lycopersicum 'Heinz 1706' showed that considering the number of genes on each chromosome there was a relatively higher concentration of these defence genes on chromosomes 1, 5, 8, 9 and 10. Intriguingly, there was no overlap with previously analysed genomic locations of domestication sweeps, but on chromosomes 1 (2), 2 (3) and 8 (4) there was an overlap with the genomic locations of improvement sweeps analysed and described in another recent study (Lin et al, 2014) (Fig. 2A).…”
Section: Selection Of Genes Involved In Tomato Defence Responsessupporting
confidence: 53%
“…Ripening involved genes, such as GR or HP1, are clearly independent of the common symbiotic pathway (Oldroyd 2013) and are probably a more recent evolutive acquisition originated by the selection for fleshy fruit characteristics. Such an interpretation, if validated, may suggest that plants selected for fruit traits of human interest, as fruit weight (Lin et al 2014), were also positively selected for their mycorrhizal systemic responsiveness. This could pave the way to investigate the role of AMF in tomato crop selection history.…”
Section: Resultsmentioning
confidence: 97%
“…(iv) Neolycopersicon group containing only Solanum penellii, which was considered to be sister to the rest of the section based on its lack of the sterile anther that occurs as a morphological synapomorphy in S. habrochaites and the rest of the core tomatoes 8 . More recent studies using conserved orthologous sequence markers (COSII) 11 , genome-wide single nucleotide polymorphisms (SNPs) 7,12 and genomic repeat elements 13 have largely supported previous hypotheses with respect to major clades within the tomatoes, although individual species relationships are less clear cut for some taxa. Thus, given the general acceptance of this informal classification, in the present study we will often use it as reference in order to better clarify the results here presented.…”
Section: Introductionmentioning
confidence: 92%